Distinct reorganization of collagen architecture in lipopolysaccharide-mediated premature cervical remodeling†. Issue 1 (17th November 2017) - Nallasamy, Shanmugasundaram; Akins, Meredith; Tetreault, Breanna; Luby-Phelps, Kate; Mahendroo, Mala
Abstract: Previous work has identified divergent mechanisms by which cervical remodeling is achieved in preterm birth (PTB) induced by hormone withdrawal (mifepristone) or lipopolysaccharide (LPS). Our current study aims to document how collagen architecture is modified to achieve premature cervical remodeling in mice treated with LPS as a model of infection-induced inflammation. Cervices were collected on gestation day (d) 15 from mice with premature cervical ripening induced by LPS and compared to d15 and d18 controls as well as a hormone withdrawal PTB model. Second harmonic generation (SHG) and electron microscopy were utilized for visualization of collagen morphology and ultrastructure. LPS-mediated premature cervical ripening is characterized by unique structural changes in collagen fiber morphology. LPS treatment increased the interfibrillar spacing of collagen fibrils. A preferential disruption of collagen fiber architecture in the subepithelial region compared to midstroma region was evidenced by increased pores lacking collagen signal in SHG images in the LPS-treated mice. Coinciding with this alteration, the infiltration of neutrophils was concentrated in the subepithelial stromal region as compared to midstromal region implicating the potential role of immune cells to extracellular matrix reorganization in inflammation-induced preterm cervical ripening. The current study demonstrates a preferential disorganization of collagen interfibrillar spacing and collagen fiber structure in LPS-mediated ripening. Summary Sentence: Region specific reorganization of cervical collagen structure in LPS-induced preterm birth.